Level of Knowledge, Attitude, and Behavior among Specialists of Otorhinolaryngology-Head and Neck Surgery in West Java Towards Cochlear Implants - Annisa Ramadhanti; Lina Lasminingrum; Sally Mahdiani; Arif Dermawan; Bambang Purwanto (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Hearing loss and deafness are still an issue in Indonesia, especially in West Java, with a prevalence of 2.5% and 0.06%, respectively. Cochlear implants are intended for patients with severe sensorineural hearing loss to stimulate the remaining auditory nerves. Based on their competency standards, Otorhinolaryngology-Head and Neck Surgery (ORL-HNS) Specialists are expected to be able to inform patients and families about the cochlear implantation procedures. This study aimed to explore the level of knowledge, attitudes, and behavior of ORL-HNS Specialists in West Java towards cochlear implants.Methods: This study was a descriptive study with a cross-sectional approach. Primary data were collected through a questionnaire filled out by ORL-HNS Specialists who were actively working in West Java in 2021–2022.Results: Data from 157 specialists showed that 41.4% (n=65) had good knowledge about cochlear implants, and 43.9% (n=69) had adequate knowledge, however, 62.4% (n=98) showed a negative attitude. In addition, 99.3% (n=156) showed good behavior.Conclusions: ORL-HNS Specialists in West Java have a sufficient level of knowledge, negative attitude, and good behavior towards cochlear Implants. The negative attitude of the specialists need to be bettered, updating their knowledge about how cochlear implants work and their effectiveness for patients with hearing impairments might give them a new perspective and hopefully change their attitude towards cochlear implants.